KONSEP WARIA DALAM TELEVISI INDONESIA; Sebuah Kajian Dekonstruktif - Sun Fatayati (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2014)
This article explains about shemale (transgender subject) which have negative images in around of our society. This is because of the society social construction that used to seeing life of transsexual who always synonymous with prostitution. This study explains the deconstruction toward shemale (transgender subject) which is constructed by television’s programs. This study looked at not only the use of media of transgender subject on television, but it also sought to identificate the deconstruction of transgender subject on television’s program. In the fact, the values of Islam considered that being a transgender is a big sin. This study uses a Semiotic theory of Charles Sanders Pierce which cleaves the symbol through a triangle of meaning, they are representament, object, and interpretant. Then, the detail meaning which is gained after it is classified based on the kind of objects such as index icon and symbol. After we construct it, we will analyze based on the rules of deconstruction (Binner opposition and Differance) according to Jaqcues Derrida.